Analysis of the Incidence of Neonatal Umbilical Cord Infections - Nursasmita, Rizqi; Karlina; Andi Julia Rifiana (International Health Sciences Journal, 2025)
The number of neonatal deaths this year has increased very significantly compared to last year, namely 265 deaths. Neonatal deaths contribute 59% to infant deaths, where one of the biggest causes is neonatal tetanus, which is an umbilical cord infection that occurs in babies. Therefore, proper umbilical cord care is needed to prevent umbilical cord infections. Objective: The aim of this research is to analyze the incidence of umbilical cord infections at Hospital X, South Jakarta. Methods: Using quantitative research methods with a case control approach design. With 15 cases and 30 controls. The research instrument used a questionnaire on knowledge, attitudes, maternal support and how to care for the umbilical cord. Statistical tests use the Chi-Square test. Result: With the research results, the average age of respondents is 20-35 years, the mother's level of knowledge is good (47.5%), the mother's attitude (62.2%), family support (60%), and how to care for the umbilical cord is good (57, 8). Conclusion: There is no significant relationship between maternal age, p-value 0.545 and the incidence of umbilical cord infection, there is a significant relationship p-value 0.000 of knowledge, maternal attitudes, family support, how to care for the umbilical cord and the incidence of infection. Suggestions for workplaces can be used as input to improve nursing interventions such as education about umbilical cord care, for mothers who have neonates it is hoped that the pocket book can be used as a reference in umbilical cord care, for educational institutions can facilitate post-partum mothers through health education, suggestions for future researchers are to consider other variables that might influence the incidence of umbilical cord infections, such as environment and culture.